Better outcome of COVID‐19 positive kidney transplant recipients during the unremitting stage with optimized anticoagulation and immunosuppression. Issue 6 (12th May 2021) - AlOtaibi, Torki M.; Gheith, Osama A.; Abuelmagd, Mohammed M.; Adel, Mohammed; Alqallaf, Ahmed K.; Elserwy, Nabil A.; Shaker, Mohamed; Abbas, Ahmad M.; Nagib, Ayman M.; Nair, Prasad; Halim, Medhat A.; Mahmoud, Tarek; et al.
Abstract: Introduction: COVID‐19 is an ongoing pandemic with high morbidity and mortality and with a reported high risk of severe disease in kidney transplant recipients (KTR). Aim: We aimed to report the largest number of COVID‐19‐positive cases in KTR in a single center and to discuss their demographics, management, and evolution. Methods: We enrolled all the two thousand KTR followed up in our center in Kuwait and collected the data of all COVID‐19‐positive KTR (104) from the start of the outbreak till the end of July 2020 and have reported the clinical features, management details, and both patient and graft outcomes. Results: Out of the one hundred and four cases reported, most of them were males aged 49.3 ± 14.7 years. Eighty‐two of them needed hospitalization, of which thirty‐one were managed in the intensive care unit (ICU). Main comorbidities among these patients were hypertension in 64.4%, diabetes in 51%, and ischemic heart disease in 20.2%. Management strategies included anticoagulation in 56.7%, withdrawal of antimetabolites in 54.8%, calcineurin inhibitor (CNI) withdrawal in 33.7%, the addition of antibiotics in 57.7%, Tocilizumab in 8.7%, and antivirals in 16.3%. During a follow‐up of 30 days, the reported number of acute kidney injury (AKI) was 28.7%, respiratory failure requiring oxygen therapy 46.2%, and overall mortality rate was 10.6% with hospital mortality of 13.4% including an ICU mortality rate of 35.5%. Conclusion: Better outcome of COVID‐19‐positive KTR in our cohort during this unremitting stage could be due to the younger age of patients and early optimized management of anticoagulation, modification of immunosuppression, and prompt treatment of secondary bacterial infections. Mild cases can successfully be managed at home without any change in immunosuppression.